Behavioral risk dalam investasi: Bias psikologis dan dampaknya terhadap keputusan investasi - fitrohcahya, rahmadani aidil (Maliki Interdisciplinary Journal, 2025)
Money is a very important medium of exchange in meeting various community needs, and in its development, investment has become one way to earn money productively. Although in theory investment decisions should be taken rationally, in reality investors are often influenced by psychological biases that form behavioral risk. This study discusses various forms of psychological bias that influence investment decisions, such as overconfidence, herd behavior, loss aversion, and anchoring bias. These biases cause deviations in the rational decision-making process and have the potential to cause negative impacts, such as overtrading, panic selling, and inefficient investment decisions. An explanation of each bias is accompanied by characteristics, case examples, and their impacts on investment strategies and market stability. This study emphasizes the importance of financial literacy and awareness as an effort to mitigate behavioral bias so that investors can make wiser, more measured, and long-term oriented decisions in facing complex market dynamics.